2011
DOI: 10.1039/c1ee01088c
|View full text |Cite
|
Sign up to set email alerts
|

Towards understanding the nanofluidic reverse electrodialysis system: well matched charge selectivity and ionic composition

Abstract: The widespread use of tiny electrical devices, from microelectromechanical systems (MEMS) to portable personal electronics, provides a new challenge in the miniaturization and integration of power supply systems. Towards this goal, we have recently demonstrated a bio-inspired nanofluidic energy harvesting system that converts salinity gradient energy from the ambient environment into sustainable electricity with single ion-selective nanopores (Adv. Funct. Mater. 2010, 20, 1339. The nanofluidic reverse electrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
149
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 185 publications
(156 citation statements)
references
References 58 publications
(62 reference statements)
5
149
0
2
Order By: Relevance
“…In nanofluidic systems, the asymmetric geometry functions not only as a pathway for molecular transportation, but also provides a geometric kinetic constraint that possibly induces a unidirectional diffusive flow through the nanopore [59,60]. Studies on the application of geometryinduced asymmetric diffusion for bio-inspired energy conversion and oil/water separation are currently underway in our lab [61][62][63][64].…”
Section: Resultsmentioning
confidence: 98%
“…In nanofluidic systems, the asymmetric geometry functions not only as a pathway for molecular transportation, but also provides a geometric kinetic constraint that possibly induces a unidirectional diffusive flow through the nanopore [59,60]. Studies on the application of geometryinduced asymmetric diffusion for bio-inspired energy conversion and oil/water separation are currently underway in our lab [61][62][63][64].…”
Section: Resultsmentioning
confidence: 98%
“…3a-c). It has been proven that the net diffusion current stems only from the charge separation and concentration distribution within the electrical double layer 24 , and therefore the total current can be expected to increase more rapidly within small pores in the double-layer overlap range compared with larger pore sizes (Fig. 3d).…”
Section: Letter Researchmentioning
confidence: 99%
“…In KCl solution, K + , which has the highest diffusion coefficient, yielded the maximum power, whereas LiCl yielded the lowest power. In this experiment, the highest power obtained was 45pW 11 . They also observed that the pH value of electrolyte influenced the surface charge of membranes or nanochannels 12 .…”
Section: Introductionmentioning
confidence: 93%